2019
DOI: 10.1101/733147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The finger 2 tip loop of Activin A is required for the formation of its non-signaling complex with ACVR1 and type II Bone Morphogenetic Protein receptors

Abstract: Activin A functions in BMP signaling in two ways: it either engages ACVR1B to activate Smad2/3 signaling or binds ACVR1 to form a non-signaling complex (NSC). Although the former property has been studied extensively, the roles of the NSC remain unexplored. The genetic disorder fibrodysplasia ossificans progressiva (FOP) provides a unique window into ACVR1/Activin A signaling because in that disease Activin can either signal through FOPmutant ACVR1 or form NSCs with wild type ACVR1. To explore the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Sequences both in the receptors and the ligand determine binding specificity and strength. Recent studies have suggested that the finger 2 tip loops in activin A and GDF11 are important for their type I receptor binding specificities [44,45]. Moreover, in some cell types, only mutated ALK2, such as the variant encoded by ACVR1 (R206H), has been shown to relay a signal to SMAD1/5 after activin binding [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Sequences both in the receptors and the ligand determine binding specificity and strength. Recent studies have suggested that the finger 2 tip loops in activin A and GDF11 are important for their type I receptor binding specificities [44,45]. Moreover, in some cell types, only mutated ALK2, such as the variant encoded by ACVR1 (R206H), has been shown to relay a signal to SMAD1/5 after activin binding [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of responsiveness was not due to competition between activin A and BMPs for binding to ACVR1-containing receptor complexes (see refs. (7,10,11)), as globally recombined R26 ACVR1/+ mice were refractile to injury-induced HO even under conditions of antibody-mediated inhibition of activin A (unpublished observations). These data could indicate that BMPs that signal through ACVR1, such as BMP5, BMP6 and BMP7 (37,55,56), are not available at sufficient levels in skeletal muscles and associated connective tissues to elicit an osteogenic response from presumptively hyper-responsive cells.…”
Section: Discussionmentioning
confidence: 85%
“…Examples include sensitizing cells to BMP ligands that signal through ACVR1 (37,51), reducing SMAD2/3 signaling by sequestration of activins into inactive complexes (7,11), or dampening signaling by other TGFβ family ligands and type I receptors by reducing availability of shared . CC-BY-NC-ND 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations